The Elementary Student’s Digital Literacy to Supporting Gold Generation in 5.0 Society Era - Raden Kania; Tifani Intan Solihati; Nur Hidayanti; Rudianto Rudianto; Ina Rohiyatussakinah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The negative impact of online learning is felt, such as the occurrence of loss of learning, the attitude of students who are less polite, lazy, widespread violence, pornography and porn action, addiction to gadgets, etc. For internet media to be used properly, digital literacy skills are needed. Mitchell Kapoor stated that the younger generation has the skills to access digital media, but it has not been matched with the skills to acquire the right information to develop themselves, because the diversity of media and types of information sometimes confuses them. The success of building digital literacy is one indicator of achievement in the fields of education and culture. Introduction to Digital Literacy which was held at SDN Pasir Attorney, Kec. Koroncong, Kab. Pandeglang. The activity was held in collaboration with the UNBAJA Library, and KKM Unbaja students group. 22, Bank Indonesia (BI), Rajagrafindo Persada Publisher, Pasir Prosecutors Village Apparatus, and Pasir Prosecutors Elementary School which was attended by 100 students from grades 3 to 6. The methods used were lectures, questions and answers, games, role-playing, and hands-on practice. The initial condition is that only a few students know about digital literacy (healthy internet, digital ethics, and e-resources. After the activity is carried out, students can practice searching for information that is appropriate, polite, and ethical, they have insight into the diversity of information sources, both knowledge, sources of learning, practice videos, learning tutorials, and recreational media events such as films and videos that are appropriate for their age.